Carding Crime in Makassar City: Juridical Review As an Issues of Cybercrime - Muh. Fandi Nursalam,; Sinilele, Ashar; Istiqamah, (Alauddin Law Development Journal, 2024)
This study analyzes the juridical review of carding crime in Makassar City as part of cybercrime. The purpose of this study is to provide scientific benefits in the field of legal studies as well as provide practical and academic input for authors and interested parties to understand the criminal law arrangements against carding crimes and countermeasures. The research method used is the method of normative juridical literature, referring to legal norms in legislation, literature, expert opinions, and papers. The results showed that the laws that are the focus of the study are Law No. 19 of 2016 on amendments to Law No. 11 of 2008 on information and electronic transactions, as well as the Criminal Code (KUHP).